ANALISIS PENYELESAIAN PROYEK PENGASPALAN JALAN DESA (STUDI PADA CV. DITA JAYA LESTARI DI KABUPATEN KUANTAN SINGINGI) - Ardhian Saputra; Iwan Nauli Daulay; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Research purpose is to know the form of networking or network planning, knowing work or activities anything who is critical and to know the probability completion of the village road paving project at Sei Kelelawar at CV. Dita Jaya Lestari in Kuansing. Research in it consists of a single bound namely side variables completion of project like road village ( study at CV. Dita Jaya Lestari in Kuansing) (Y) and three variables free namely critical work (X1), network PERT/CPM (X2), & Probability (X3). Data from this research is time estimation of completion of project like road and three time estimation are optimistic that the time namely, realistic time, and pessimistic time and analysis of data this research using methods Critical Path Method (CPM) and methods project evaluation and review technique (PERT). Based on the data process can be seen that a village road paving project realization Sei Kelelawar in Kuansing greatly exceeds the target and not in accordance with the implementation of planning time, so the time spent in the village road paving project completion Sei Kelelawar in Kuansing is not very optimal, with the value of Z for probability on a day to 113 at 99,9% with a standard deviation is 3,83. This is because too the value of the standard deviation of up to 130 days.Keywords : Completion, Critical Works, Network and Probability.